Transcriptome analysis revealed changes of multiple genes involved in immunity in Cynoglossus semilaevis during Vibrio anguillarum infection. Issue 1 (March 2015) - Zhang, Xiang; Wang, Shaolin; Chen, Songlin; Chen, Yadong; Liu, Yang; Shao, Changwei; Wang, Qilong; Lu, Yang; Gong, Guangye; Ding, Shaoxiong; Sha, Zhenxia
Abstract Half-smooth tongue sole (Cynoglossus semilaevis) is one of the most valuable marine aquatic species in Northern China. Given to the rapid development of aquaculture industry, the C. semilaevis was subjected to disease-causing bacteria Vibrio anguillarum. It therefore is indispensable and urgent to understand the mechanism of C. semilaevis host defense against V. anguillarum infection. In the present study, the extensively analysis at the transcriptome level for V. Anguillarum disease in tongue sole was carried out. In total, 94, 716 high quality contigs were generated from 75, 884, 572 clean reads in three libraries (HOSG, NOSG, and CG). 22, 746 unigenes were identified when compared with SwissProt, an NR protein database and NT nucleotide database. 954 genes exhibiting the differentially expression at least one pair of comparison in all three libraries were identified. GO enrichment for these genes revealed gene response to biotic stimulus, immune system regulation, and immune response and cytokine production. Further, the pathways such as complement and coagulation cascades and Vibrio cholerae infection pathways were enriched in defensing of pathogen. Besides, 13, 428 SSRs and 118, 239 SNPs were detected in tongue sole, providing further support for genetic variation and marker-assisted selection in future. In summary, this study identifies several putative immune pathways and candidate genes deserving further investigation in the context of development of therapeutic regimens and lays the foundation for selecting resistant lines of C. semilaevis against V. anguillarum.